Conspiracy Beliefs and Violent Extremist Intentions: The Contingent Effects of Self-efficacy, Self-control and Law-related Morality - Rottweiler, Bettina (Terrorism and political violence, 2022)
This study analyzes the effects of conspiracy beliefs on violent extremist intentions. More specifically, we investigate whether the relationship between conspiracy beliefs and violent extremism depends upon individual characteristics such as varying levels of self-efficacy, self-control, and law-relevant morality. Variable interactions examine where conspiracy beliefs exert strong effects on violent extremist intentions. The analysis is based on a German nationally representative survey (N = 1502). To our knowledge, it is the first and only nationally representative survey carried out in violent extremism research.Our results confirm that a stronger conspiracy mentality leads to increased violent extremist intentions. However, this relationship is contingent on several individual differences. The effects are much stronger for individuals exhibiting lower self-control, holding a weaker law-relevant morality, and scoring higher in self-efficacy. Conversely, when stronger conspiracy beliefs are held in combination with high self-control and a strong law-relevant morality, violent extremist intentions are lower. Such individual features thus constitute interactive protective factors for violent extremism. These results have important implications for practice in the area of violent extremism risk assessment and management. Conceptually, the results demonstrate the need to further elaborate the conditional effects of certain risk as well as protective factors for violent extremism.